2018
DOI: 10.1016/j.sjbs.2017.12.005
|View full text |Cite
|
Sign up to set email alerts
|

Autosomal single-gene disorders involved in human infertility

Abstract: Human infertility, defined as the inability to conceive after 1 year of unprotected intercourse, is a healthcare problem that has a worldwide impact. Genetic causes of human infertility are manifold. In addition to the chromosomal aneuploidies and rearrangements, single-gene defects can interfere with human fertility. This paper provides a review of the most common autosomal recessive and autosomal dominant single-gene disorders involved in human infertility. The genes reviewed are ,, ,, ,, ,, and genes. These… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 96 publications
1
15
0
Order By: Relevance
“…A missense heterozygous mutation involving c. 3G → A transition and two heterozygous frameshift mutations named c. 666delC and c. 390delG were reported [17]. The following were also reported: p. Pro311Leu, p. Arg191Cys, p. Gly121Ser, p. Asp238Asn, and p. Gly123Ala/p.…”
Section: Genes Predisposing To Syndromic Infertilitymentioning
confidence: 99%
See 2 more Smart Citations
“…A missense heterozygous mutation involving c. 3G → A transition and two heterozygous frameshift mutations named c. 666delC and c. 390delG were reported [17]. The following were also reported: p. Pro311Leu, p. Arg191Cys, p. Gly121Ser, p. Asp238Asn, and p. Gly123Ala/p.…”
Section: Genes Predisposing To Syndromic Infertilitymentioning
confidence: 99%
“…A heterozygous deletion called 643delA, and a heterozygous genetic change known as T657C was identified among Iranian women with recurrent pregnancy losses [17].…”
Section: Sycp3 (Synaptonemal Complex Protein 3)mentioning
confidence: 99%
See 1 more Smart Citation
“…These mutations are generally autosomal recessive and inherited from fertile parents in homozygous, compound heterozygous or hemizygous form. However, autosomal dominant monogenic mutations can also precipitate a state of infertility including SYCP3 (Synaptonemal complex protein 3), NR5A1 (nuclear receptor subfamily 5 group A member 1) and the WT1 (Wilms' tumor 1) gene (68). A recent detailed analysis of the genetic causes of non-obstructive azoospermia (NOA) concluded that the largest single category of monogenic defects detected in NOA patients comprises genes involved in different stages of spermatogenesis, mostly functioning in the prophase of the first meiotic division as well as transcriptional and endocrine regulators of reproduction (67).…”
Section: Mutations Affecting the Testes And Excurrent Ductsmentioning
confidence: 99%
“…In fact, long been known chromosomal syndromes associated with infertility diagnosed by karyotype analysis, but only in recent years studies have been conducted on specific chromosomal regions and identified single genes linked to infertility problems. About 30% of infertility cases are still apparently sine causa and it is difficult for these to be syndromic conditions, but rather for conditions in which the reproductive defect is the only diagnostic indication [ 25 , 26 ]. Knowledge of the molecular defect attributable to single genes could lead to the development of targeted therapies to correct the genetic defect.…”
Section: Introductionmentioning
confidence: 99%